ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DITINJAU DARI GAYA BELAJAR TIPE KOLB PADA MATERI BILANGAN BULAT - Nanda Iftinan Hakima (Universitas Pekalongan, 2020)
Every student has a different style of thinking between one individual and another individual. Thinking styles that need to be considered are based on how each student's learning style, by understanding student learning styles can improve critical thinking skills based on their individual learning styles. One of them is Kolb's learning style. The purpose of the study was to determine and analyze students' critical thinking skills in terms of the Kolb type learning style on integer material. This type of research is a qualitative descriptive study. The objects in this study were students of class VII I of SMP N 1 Tukdana Indramayu and the subjects in this study were representatives of two students from each type of Kolb learning style. The method used is exploratory research. The results showed the critical thinking ability of students with learning styles Diverger, Assimilator, Coverger, and Accomodator have different characteristics in analyzing questions, finding answers, conclusions, terms and other alternatives. It is necessary to improve critical thinking skills in each learning style.